2010
DOI: 10.1159/000283946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indomethacin Infused over 30 Minutes on Cerebral Fractional Tissue Oxygen Extraction in Preterm Newborns with a Patent Ductus Arteriosus

Abstract: Background: A significant patent ductus arteriosus (PDA) is a common finding in the first days of life and, if persistent, is associated with an increased morbidity and mortality in the preterm newborn. Objectives: Our aim was to investigate, using near-infrared spectroscopy, the effect of indomethacin on the fractional tissue (cerebral) oxygen extraction (FTcOE) in a group of preterm newborns undergoing medical treatment for a PDA. Methods: This is a prospective, observational study. A cohort of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
1
10
1
1
Order By: Relevance
“…Furthermore, our subgroup analysis indicates that responses to indomethacin may differ among racial groups. Our findings in neonates in the first day of life complement those of Keating et al 11 who reported a similar magnitude increase in fractional cerebral oxygen extraction in neonates being treated for a clinically significant ductus arteriosus at 2 to 11 days old.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our subgroup analysis indicates that responses to indomethacin may differ among racial groups. Our findings in neonates in the first day of life complement those of Keating et al 11 who reported a similar magnitude increase in fractional cerebral oxygen extraction in neonates being treated for a clinically significant ductus arteriosus at 2 to 11 days old.…”
Section: Discussionsupporting
confidence: 90%
“…Applications in preterm infants included cerebral monitoring during the first days of life 7,14,20 or during therapy of a patent ductus arteriosus. 11,13 We tested, if monitoring of cerebral StO 2 is feasible in VLBW infants during neonatal resuscitation during the first minutes after delivery. In our study, at the age of 1 minute the range of cerebral StO 2 was 31 to 49% and increased to a steady state of 61 to 84% B7 min after birth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in preterm infants for various healthcare conditions such as respiratory distress syndrome, 7 red blood cell transfusion, 8 desaturations, 9 indomethacin therapy 10,11 or ligation of a patent ductus arteriosus 12,13 and during the critical first days of life. [14][15][16][17] Major determinants of the regional tissue oxygen saturation are changes in SpO 2 , regional perfusion, regional blood volume and metabolic rate of oxygen utilization.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS studies have shown that indomethacin can alter cerebral oxygenation such as the fractional tissue oxygen extraction, although the magnitude of the changes appears to depend on the infusion protocol (5,14,15). Interpreting cerebral oxygenation in terms of energy metabolism is difficult because cerebral blood oxygenation depends on the balance between oxygen delivery and consumption.…”
mentioning
confidence: 99%